2019
DOI: 10.1002/art.40759
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab Fails to Show Efficacy in a Phase III Axial Spondyloarthritis Program: The Importance of Negative Results

Abstract: In this issue of Arthritis & Rheumatology, Deodhar et al report negative phase III study results for ustekinumab in axial spondyloarthritis (SpA) (1). Ustekinumab is an interleukin-12 (IL-12)/IL-23 inhibitor approved for the treatment of psoriasis, psoriatic arthritis (PsA), and Crohn's disease. PsA has close clinical and genetic associations with axial SpA, including genetic association with variants in the IL-23 receptor signaling pathway. In addition, ustekinumab demonstrated promising results in a phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 8 publications
0
22
0
3
Order By: Relevance
“…For treatment of the spondylitis component of PsA, we rely on data from axSpA trials, which also may not be accurately extrapolatable. Trials of the IL-12/23 inhibitor ustekinumab and the IL-23 inhibitor risankizumab have failed in ankylosing spondylitis 13. Even though these agents have demonstrated benefit and been approved for PsA, their ability to benefit the spinal component of PsA remains unproven and needs to be tested.…”
Section: Resultsmentioning
confidence: 99%
“…For treatment of the spondylitis component of PsA, we rely on data from axSpA trials, which also may not be accurately extrapolatable. Trials of the IL-12/23 inhibitor ustekinumab and the IL-23 inhibitor risankizumab have failed in ankylosing spondylitis 13. Even though these agents have demonstrated benefit and been approved for PsA, their ability to benefit the spinal component of PsA remains unproven and needs to be tested.…”
Section: Resultsmentioning
confidence: 99%
“…IL-12/23p409–11 and IL-23p19 inhibitors are effective in PsA22 23 but not AS,13 24 while IL-17 inhibition is effective in AS and PsA, inclusive of axial manifestations 25 26. Specific to AS and PsA, it has been postulated that differing biologic mechanisms in the spine, where IL-23-independent production of IL-17 may occur, versus the periphery results in differential responses to IL-23 inhibition 27 28. Indeed, in a recently conducted prospective evaluation of >2000 patients with AS or PsA, AS patients, with or without psoriasis, differed demographically, genetically, clinically and radiographically from patients with axial PsA, leading the authors to conclude that axial PsA appears to be a distinct entity 29.…”
Section: Discussionmentioning
confidence: 99%
“…In future, a formal evaluation of the functional prediction of a given polymorphism prior to assumption of pathogenetic association would seem prudent. It has also been suggested that perhaps IL-23-independent IL-17A production may be crucial in the observed divergent therapeutic response to two drugs targeting the same pathway though the evidence here is sparse 32,33 . Furthermore, pharmacodynamics and tissue drug penetration remain theoretical challenges or as yet misunderstood pathologic events in axial disease.…”
Section: Comparison Of Different Targeted Therapiesmentioning
confidence: 93%